NILAI FILANTROPI: SEBUAH TINJAUAN PELAKSANAAN AKAD QARDHUL HASAN DI MASA PANDEMI - Murdianto, Wahidin (Program Studi Manajemen Zakat dan Wakaf, 2021)
BMT Tumang Boyolali is a non-bank Islamic financial institution. Baitul Maal wa Tamwil is an institution that runs two fields, namely business through Tamwil and social through maal. One of the social programs at Baitul Maal at BMT Tumang is an economic empowerment program, namely Pokusma. The main problem raised regarding the implementation of the qardhul hasan contract used in the maal program is reviewed with maqashid shari'ah during the covid-19 pandemic, namely the suitability of the implementation of the contract with existing provisions and the fulfillment of maqashid shari'ah values in the use of the qardhul hasan contract in the field of Maal BMT Tumang Boyolali Center during the covid-19 pandemic. Thus it will be known how the qardhul hasan contract is used in the maal program in the midst of the Covid-19 pandemic. The review of maqashid shari'ah on the implementation of the qardhul hasan contract during the covid-19 pandemic will reveal the extent to which the values of maqashid sharia and maqashid qardh are being fulfilled. BMT Tumang Pusat Boyolali merupakan lembaga keuangan syariah non Bank. Baitul Maal wa Tamwil merupakan lembaga yang menjalankan dua bidang, yakni bisnis melalui tamwil dan sosil melalui maal. Salah satu program sosial pada baitul maal di BMT Tumang adalah program pemberdayaan ekonomi yaitu pokusma. Masalah utama yang diangkat perihal pelaksanaan akad qardhul hasan yang digunakan pada program maal ditinjau dengan maqashid syariah di masa pandemi covid-19 yakni kesesuaian pelaksanaan akad dengan ketentuan yang ada dan pemenuhan nilai-nilai maqashid syariah dalam penggunaan akad qardhul hasan dalam bidang maal BMT Tumang Pusat Boyolali di masa pandemi covid-19. Dengan demikian akan diketahui bagaimana penggunaan akad qardhul hasan pada program maal di tengah pandemi Covid-19. Tinjauan maqashid syariah terhadap pelaksanaan akad qardhul hasan di masa pandemi covid-19 akan diketahui sejauh mana pemenuhan nilai-nilai maqashid syariah dan maqashid qardh.